From common values to complementary interests: For a new conception of Germany's and the EU's relations with Latin America and the Caribbean - Günther Maihold; Tania Muscio Blanco; Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2023)
The Covid-19 pandemic and Russia's war of aggression against Ukraine have posed major challenges - in different ways - to Latin American and Caribbean (LAC) countries as well as to the European Union (EU). At the same time, these international crises have revealed how little resilience there is in the narratives that are supposed to inform normative relations between the two regions: shared values, strategic partnership, and dialogue at eye level. In fact, this rhetoric is based on wishful thinking and does less and less justice to the reality of mutual relations. Common ground is crumbling, and there is a lack of projects that give meaning and purpose to cooperation. Such projects would have a chance of success especially if divergent views were addressed and mutual expectations were openly negotiated. Instead of building on commonalities, future-oriented cooperation should rely more on complementarities - within the framework of varying formats.
Keywords: 320; Germany; EU; Latin America; Caribbean (LAC); Covid-19 pandemic; Russia's war of aggression against Ukraine